Amish Secrets: Her Brother's Keeper - Book 1 - Wiseman, Beth, 1962- (Nashville : Thomas Nelson, 2015)
"Charlotte Dolinsky is not above playing dress-up and telling a few lies to find out what happened to her only brother. In fact, that is exactly what shes come to Lancaster County to do. Now, calling herself Mary and slipping on a kapp, Charlotte will lie her way into the confidence of anyone who knows why Ethan had to die. Unless she gets found out first"--Page 4 of cover.
Keywords: Amish -- Fiction; Brothers -- Fiction. -- Death; Impersonation -- Fiction; Man-woman relationships -- Fiction; Christian fiction; Romance fiction